Successful Establishment of Plasmids R1 and pMV158 in a New Host Requires the Relief of the Transcriptional Repression of Their Essential rep Genes - Ruiz-Masó, José Á.; Luengo, Luis M.; Moreno-Córdoba, Inmaculada; Díaz-Orejas, Ramón; del Solar, Gloria (Frontiers in Microbiology, 2017)
Although differing in size, encoded traits, host range, and replication mechanism, both narrow-host-range theta-type conjugative enterobacterial plasmid R1 and promiscuous rolling-circle-type mobilizable streptococcal plasmid pMV158 encode a transcriptional repressor protein, namely CopB in R1 and CopG in pMV158, involved in replication control. The gene encoding CopB or CopG is cotranscribed with a downstream gene that encodes the replication initiator Rep protein of the corresponding plasmid. However, whereas CopG is an auto-repressor that inhibits transcription of the entire copG-repB operon, CopB is expressed constitutively and represses a second, downstream promoter that directs transcription of repA. As a consequence of the distinct regulatory pathways implied by CopB and CopG, these repressor proteins play a different role in control of plasmid replication during the steady state: while CopB has an auxiliary role by keeping repressed the regulated promoter whenever the plasmid copy number is above a low threshold, CopG plays a primary role by acting coordinately with RNAII. Here, we have studied the role of the regulatory circuit mediated by these transcriptional repressors during the establishment of these two plasmids in a new host cell, and found that excess Cop repressor molecules in the recipient cell result in a severe decrease in the frequency and/or the velocity of appearance of transformant colonies for the cognate plasmid but not for unrelated plasmids. Using the pMV158 replicon as a model system, together with highly sensitive real-time qPCR and inverse PCR methods, we have also analyzed the effect of CopG on the kinetics of repopulation of the plasmid in Streptococcus pneumoniae. We show that, whereas in the absence of CopG pMV158 repopulation occurs mainly during the first 45 min following plasmid transfer, the presence of the transcriptional repressor in the recipient cell severely impairs the replicon repopulation and makes the plasmid replicate at approximately the same rate as the chromosome at any time after transformation, which results in maximal plasmid loss rate in the absence of selection. Overall, these findings indicate that unrepressed activity of the Cop-regulated promoter is crucial for the successful colonization of the recipient bacterial cells by the plasmid.